Viralitas Surat Al-Fatihah Dewa 19: Negosiasi Makna Agama di Media Sosial - Iman Mukhroman (MUKASI: Jurnal Ilmu Komunikasi, 2025)
The virality of the video of Dewa 19 performing surah Al-Fatihah in a music concert has become a widespread discussion on social media, raising debates between artistic expression and the boundaries of religious sacredness. This research aims to understand how religious symbols are represented and reinterpreted in the digital popular culture space. A qualitative approach was used with netnographic methods and framing analysis of social media content responding to the video. Data was collected from comments on platforms such as YouTube, TikTok, Instagram, and Twitter, then analyzed to identify patterns of public interpretation. The results show that the video became a space of negotiation between religious expression, commodification of religious symbols, and shifting religious authority in the digital era. The emergence of polarized opinions reflects new dynamics in the relationship between religion and popular culture. The findings show that social media not only reproduces religious meanings, but also becomes a discursive arena where religious authority is challenged and negotiated. This research contributes to the study of religious communication and digital media in the contemporary era.